Pengembangan Soal Higher Order Thinking Skills (HOTS) Pada Materi Sistem Persamaan Linear Tiga Variabel (SPLTV) Kelas X SMA - Riski Ningsih; Annajmi Annajmi (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2020)
This study discusses the development of the Higher Order Thinking Skill (HOTS) test instrument, the material for the three-variable linear equation system for class X SMA. This study aims to: 1) determine the steps in developing the HOTS test instrument, 2) Knowing the validity value of the HOTS test instrument. This study uses a type of research and development (Research and Development). The development model used is the Formative Research Tessmer type development model, which consists of 2 main stages: the preliminary stage and the formative evaluation stage. In stage 1 consists of preliminary and self-evaluation. In stage 2, the formative evaluation includes prototyping. The data collection technique used was a test. The instruments used in this study were test instruments and validation sheets. Validity is known from the results of the validator's assessment on the validation sheet, which states that the test instrument has been well developed based on content (according to curriculum and material), construct (according to HOTS characteristics/indicators), language (following applicable language rules), time allocation and instructions question. Based on the prototype stage results, a predetermined quality criterion test instrument was produced, namely valid and overall suitable for use as a HOTS question